AN ANALYSIS OF PSYCHOLOGICAL ORIENTATION, COMMITMENT AND EMPLOYEE PERFORMANCE IN PUBLIC INSTITUTIONS: A CASE STUDY OF KAMPALA CITY COUNCIL AUTHORITY (KCCA), UGANDA - Nabayinda, Hasanati; Matovu, Musa (International Journal of Research -GRANTHAALAYAH, 2020)
Background: The study intended to analyze the relationship between psychological orientation, commitment and employee performance among staff in public institutions: A case study of Kampala City Council Authority (KCCA). The study tested three hypotheses; (i) there is no relationship between psychological orientation and employee commitment in KCCA; (ii) there is no relationship between commitment and employee performance in KCCA; and (iii) there is no relationship between orientation and employee performance in KCCA. A correlational research design was employed to test the relationship between the variables under study. A closed ended questionnaire was adopted to collect data for this study. Results: From the results obtained it was observed that there is a significant positive relationship between psychological orientation and commitment, r = .668, p = .015, N = 213; statistically significant positive relationship between commitment and employee performance, r = .419, p = .041, N = 213; and statistically significant positive relationship between psychological orientation and employee performance among the staff in KCCA, r = .789, p = .000; N= 213. Recommendations: The study recommends that KCCA put more efforts and resources into psychological orientation because it highly predicts employee performance than any other variable studied. It was also noted that all the variables under study were related to one another, meaning that they have statistical importance, and can be considered when improving performance of the employees at KCCA.